PENGARUH PERUBAHAN IKLIM TERHADAP KETERSEDIAAN AIR BAKU PDAM KABUPATEN LEBAK - Prasetiawan, Teddy (Jurnal Aspirasi, 2015)
PDAM Kabupaten Lebak highly depends on surface water as their only water resources. Currently, it abundantly flows in almost all region of Kabupaten Lebak. However, could it sufficiently provides the raw water in order to anticipate the improvement of service and the impact of climate change? By considering the condition of geology, hydrogeology, hydrology, and climatology, prediction is conducted to determine the availability of raw water supply for PDAM Lebak (Ciujung, Cimadur, and Cilangkahan river basin during the period from 2015 to 2050. The analysis is performed by integrating the climatological analysis using global climate models and water balance analysis using the Thornthwaite Mather method. When the analysis result meets the water demand projection of PDAM Lebak service area, it is known that raw water supply will occur in the year 2029 using B2 scenario and 2030 using A2 scenario in the Ciujung river basin, 2044 using B2 scenario and 2046 using A2 scenario in the Cimadur river basin, and 2037 using B2 scenario and 2039 using A2 scenario in the Cilangkahan river basin.